(untitled) (BioLaw Journal - Rivista di BioDiritto, 2024)
The constant growth of the world’s population has prompted agri-food production to investigate new protein alternatives. In this context, biotechnology, and in particular cellular agriculture, plays a key role in providing nutritious, safe, healthy and sustainable products. However, there are many doubts concerning the production, safety and sustainability of cell-based products. For this reason, the aim of this chapter has been to analyse each stage of the production chain, identifying and discussing the main critical points and investigating omics techniques as a tool for obtaining cellular products. Finally, the sustainability of this new production was analysed.